2020
DOI: 10.1111/jnu.12555
|View full text |Cite
|
Sign up to set email alerts
|

Nonpharmacological Clinical Effective Interventions in Constipation: A Systematic Review

Abstract: Constipation is a health condition that presents a significant problem to the people suffering from it, generally defined as fewer than three bowel movements per week, and with great prevalence and impact on quality of life in adults and elderly people (Bub, Brinckmann, Cicconetti, & Valentine, 2006;Rao et al., 2015). It affects the overall well-being of individuals, has a multifactorial character, and can be influenced by physical, psychological, physiological, emotional, and environmental factors. Studies ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
0
9
0
2
Order By: Relevance
“…Previous studies have clarified that risk factors for constipation include female sex, advanced age, medications (e.g., anticholinergics, antipsychotics), diets, comorbidities, and mental states [10][11][12]. We also showed that the risk factors of OIC were high body mass index (BMI), chemotherapy including a taxane within 1 month of evaluation of laxative effect, no use of naldemedine, and addition or switching due to insufficient prior laxatives in advanced cancer patients [9].…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Previous studies have clarified that risk factors for constipation include female sex, advanced age, medications (e.g., anticholinergics, antipsychotics), diets, comorbidities, and mental states [10][11][12]. We also showed that the risk factors of OIC were high body mass index (BMI), chemotherapy including a taxane within 1 month of evaluation of laxative effect, no use of naldemedine, and addition or switching due to insufficient prior laxatives in advanced cancer patients [9].…”
Section: Introductionmentioning
confidence: 69%
“…Variables associated with potential risk factors for OIC were extracted from electronic medical records and used for regression analysis. Variables extracted were factors considered as potentially affecting OIC based on previous studies [1,[9][10][11][12][13] or clinically rational mechanisms, including demographic data (age, BMI, body surface area [BSA]), clinical data (Eastern Cooperative Oncology Group performance status [ECOG-PS], and stage of cancer), medicationrelated data (chemotherapy administered within 1 month of the evaluation of naldemedine effect, anti-cancer drugs administered within 1 month of the evaluation of naldemedine effect, types of opioids, daily dose of opioid in milligrams of morphine-equivalents, concomitant laxative, concomitant use of the serotonin 5-hydroxytryptamine-3 (5-HT3) receptor antagonists, naldemedine prescription within 2 days of opioid initiation, and addition of or switching to naldemedine due to insufficient efficacy of prior laxatives), and cancer type.…”
Section: Extraction Of Variablesmentioning
confidence: 99%
“…For the prevention and treatment of constipation, patients are trained about fluid and fiber intake and lifestyle changes at the first stage, and if constipation complaint persists, laxatives are recommended (Berman et al, 2016; Fritz, 2017; Huang et al, 2015). Laxatives, enemas, suppositories, and surgical treatments used in the treatment of constipation are expensive (Pinto et al, 2020). It is estimated that 28% of laxative users are not satisfied with them and the cost of treatment reaches 800 million dollars annually (Blesser et al, 2005; Müller-Lissner et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Revisão sistemática que avaliou a efetividade de intervenções não farmacológicas concluiu que, apesar dos estudos primários apresentarem amostras pequenas e com baixa evidência que permitiria a comparação entre os grupos, essa forma de manejo pode ser efetiva, principalmente, se houver envolvimento dos pacientes 15 .…”
Section: Medidas Não Farmacológicasunclassified